EXPLORING CHALLENGES, BENEFITS AND STRATEGIES OF TELEGRAM IMPLEMENTATION IN TEACHING PROCESS DURING COVID-19 PANDEMIC AT SMP NEGERI 1 TANUNG BATU, OGAN ILIR - Septiana Veronika; Baginda Simaibang; Artanti Puspita Sari (Esteem Journal of English Education Study Programme, 2022)
This study aims to improving the students’ writing ability through note-taking technique. This study applied the quasi-experiment method. The population of this study was all of the tenth grade students with a total number of 318 students and 80 students were taken as sample in experimental and control group. In collecting the data, a written test of descriptive paragraph was used, and the data were analysed by using SPSS 23. The result of this study showed that experimental group students’ average score in pre-test was 65.10 and in post-test it was 72.26 while in control group, students’ average score in pre-test 66.03 and in post-test it was 69.88. the value t-obtained was 3.082 which was higher than the value of t-table 2.000 at the significant level 0.05 in two tailed test with 78 (df). It was assumed that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. It means that there was significant difference between the students achievement in writing descriptive paragraph.